Resources used by Lebanese Secondary Physics Teachers' for Teaching Electricity: Types, Objectives and Factors Affecting their Selection - Bassel Chazbeck; Zalpha Ayoubi (Seyit Ahmet Kıray, 2018)
The purpose of this research was to study the system of resources, the objectives of their use and the factors that affect the selection and integration of the different resources by Lebanese secondary physics teachers in their teaching in general and for teaching Electricity in particular. For this aim, a qualitative approach was used and the research was designed as a collective case study where four teachers were purposefully selected. Interviews and classroom observations were the main data collection tools. Results showed that teachers used different types of resources: Paper resources, audio-visual resources, object resources, and evoked resources to elaborate their teaching activities. They paid a particular attention to the experimental activity using object and audio-visual resources to enhance students' comprehension of Physics concepts. Moreover, teachers referred to the virtual laboratory to be more efficient than the real lab at the level of precision, clarity and management, in addition to its importance for illustration at the microscopic scale. Results also revealed that the school setting, time constraints and teachers' professional knowledge are the main factors that affect the selection and the integration of resources.